The Importance of Awareness of Heritage Building's Seismic Behaviors : Specific on Pagoda-Type Structure - I. P. Ellsa Sarassantika; Ida Bagus Gede Parama Putra (Journal of Infrastructure & Facility Asset Management, 2020)
The importance of building cultural heritage. A place where historical stories, cultural values, places of worship, symbols of struggle and even now are transformed into tourist attractions and educational facilities. Keeping this building good and well maintained is a good thing to do. The purpose of this paper is to enhance awareness of the importance of knowledge about heritage buildings from the viewpoint of building structure and seismicity. In addition, as a research initiation on the performance of the existing pagoda structure in Bali, Meru, going forward. This paper reviews several studies of pagodas in numerous countries, both in terms of structural design, influence and structure on earthquake response, damage, and handling in terms of reinforcement and maintenance. Comprehensively summarizes the studies that have been done, this facilitates understanding of existing studies. With the hope of being able, to trigger and encourage studies on building cultural heritage in Indonesia in general and Bali in particular. Research on the pagoda in Bali in the future is highly expected and needs to be done.